Rapid synthesis of copper and silver nanoparticles using Zingiber officinale dried rhizome extract (Funded Work) - DEEPALI KOTHEKAR (International Journal of Pharma and Bio Sciences, 2017)
An important area of research in nanoscience is to develop reliable, nontoxic and ecofriendly methods for the synthesis of nanoparticles. Use of biological systems and biomolecules is one of the options to achieve this objective. Present work demonstrates synthesis of silver and copper nanoparticles by an economical and eco-friendly method using aqueous extract of dried rhizome powder of Zingiber officinale (Common name: ginger). Characterization of the nanoparticles was carried out using UV-Vis spectrophotometer and Quant 200 FPEI Scanning Electron Microscope. Peak absorbance due to localized surface plasmon resonance (SPR) was found to be 550 nm for silver nanoparticles and 450-500 nm for copper nanoparticles. Peak absorbance was constant for 48h for silver and 72 h for copper. Scanning electron micrographs revealed uniform spherical size, less than 100 nm for both the particles. Energy-dispersive X-ray spectroscopy confirmed the purity of nanoparticles. Phytochemical analysis showed the presence of flavonoids in the aqueous extract. The short reduction time and stability of nanoparticles by this method make it a viable alternative to chemical synthesis methods. The silver and copper nanoparticles synthesized by this method can be used in biomedical and other applications.